PP15 Consent as an ethical consideration in the conduct of prehospital ambulance randomised controlled clinical trials: a systematic review. Issue 10 (28th September 2017) - Armstrong, Stephanie; Langlois, Adele; Laparidou, Despina; Dixon, Mark; Appleton, Jason P; Bath, Philip M; Snooks, Helen; Siriwardena, A Niroshan
Abstract : Background: Clinical trials in the ambulance setting are essential for providing the basis for evidence based healthcare in the prehospital environment. As the number and complexity of ambulance trials increases the ethical issues involved in such trials. We sought to understand the main ethical considerations when conducting clinical trials in the prehospital ambulance based setting. Methods: We conducted a systematic review of ethical issues considered in randomised controlled trials in ambulance settings. A search of eight databases identified ethical issues discussed in published studies involving recruitment of ambulance service users. Four independent authors undertook abstract and full-text reviews to determine eligibility and then extracted relevant data. The data extraction concentrated on ethical considerations, with any discussion of ethics being included for further analysis. The resultant data were combined to form a narrative synthesis. Results: In all, 56 papers were identified as meeting the inclusion criteria. Issues relating to consent were the most significant theme identified. Several consent models were used ranging from informed consent to exception from informed consent (also termed waiver of consent). Type of consent differed depending on the clinical condition or the intervention being studied. The country in which the research took place did not appear to influence the type of consent, apart from the USA where exception from informed consent appeared to be most commonly used. Many studies cited international guidelines as informing their choice of consent model and diverse and sometimes confused terms were used to describe these models. Conclusions: Consent was the main ethical consideration in published ambulance based research. A wide range of terms was used to describe consent and terms were sometimes confused or used inconsistently. This suggests that standardisation of consent models and the terminology used to describe them may be helpful for researchers, ethics committees and research participants.